Fibre imaging bundles for full-field optical coherence tomography - Ford, Helen D.; Tatam, Ralph P. (IOP Publishing, 2007)
An imaging fibre bundle is incorporated into a full-field imaging OCT system, with the aim of eliminating the mechanical scanning currently required at the probe tip in endoscopic systems. Each fibre within the imaging bundle addresses a Fizeau interferometer formed between the bundle end and the sample, a configuration which ensures down lead insensitivity of the probe fibres, preventing variations in sensitivity due to polarization changes in the many thousand constituent fibres. The technique allows acquisition of information across a planar region with single-shot measurement, in the form of a 2D image detected using a digital CCD camera. Depth scanning components are now confined within a processing interferometer external to the completely passive endoscope probe. The technique has been evaluated in our laboratory for test samples, and images acquired using the bundle-based system are presented. Data are displayed either as en-face scans, parallel to the sample surface, or as slices through the depth of the sample, with a spatial resolution of about 30 Ã¯Â Âm. The minimum detectable reflectivity at present is estimated to be about 10-3, which is satisfactory for many inorganic samples. Methods of improving the signal-to- noise ratio for imaging of lower reflectivity samples are discusse
Keywords: OCT; coherence tomography; imaging bundles; coherent fibre bundles